Exploring the Wilcoxon Test in Science Education: A Literature Review of Empirical Research - Nur Indah Sari Indah; Fandi Ahmad (Indonesian Journal of Educational Science (IJES), 2025)
Wilcoxon test, a non-parametric statistical method, is often used in educational research to analyze significant differences between two groups of related data. This study explores the utilization of the Wilcoxon Test in science education research through a systematic literature review approach of empirical studies. The review included empirical research articles published in accredited scientific journals and applied the Wilcoxon Test as data analysis. The findings showed the prevalence of using the Wilcoxon Test in pre-test and post-test data analysis in experimental research design, comparative research, extension research, and development research. In addition, the study identified various variations of the Wilcoxon Test application, including the Wilcoxon Test for paired samples and the Wilcoxon Test with continuity correction. This literature review provides a comprehensive description of Wilcoxon Test applications in science education research and recommends careful consideration for researchers in selecting and applying the statistical test based on data characteristics and research objectives.